Manajemen Pengelolaan Dengan Konsep Akad Syari’ah Pada Ely Wedding House Di Era New Normal Bangil - Pasuruan - Lailatul Azizah (Universitas Airlangga, 2022)
The wedding procession has now become a sacred, expensive, and complicated procession with many stages that should be passed involving many people. It requires energy, time, and money to be prepared, while the couple has busy activities with their family or the bride and groom. To solve these problems, it needs a wedding organizer agency to handle the wedding procession smoothly. The research will analyze the business management of wedding organizers within sharia contracts. This research used a qualitative method using a case study approach to see the Ely Wedding House’s management strategies. The result of the data analysis stated that this wedding organizer was seen as having low competitors. The wedding organizer services not only do what cliens needed, but they must try to offer wedding service products to win market share and contribute ideas to new markets through various strategies, and innovations that are displayed such as business development. It includes the pre-wedding field: Packages to decorate offerings, pre-wedding packages treatment, pre-wedding photo services. So that it can influence the client to make a decision to use the services. In the competitive world of business, the emergence of wedding organizer services, both those that apply Islamic concepts or not, 1are trying to offer wedding service products to seize market share and new markets through various ways and innovations that are displayed, thus influencing customer decisions in making a decision to use their service (customer decision making) this is an integration process that combines consumer knowledge o evaluate two or more alternative behavior choices that exist through internet media that can reach consumers widely.